2011
DOI: 10.1016/s1734-1140(11)70574-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of vinpocetine in cerebrovascular diseases

Abstract: A cerebrovascular accident, or stroke, is defined as the abrupt onset of a neurological deficit, which can be due to ischemia. Cerebral ischemia is caused by a reduction in blood flow that thereby decreases cerebral metabolism. Chronic cerebral hypoperfusion leads to irreversible brain damage and plays an important role in the development of certain types of dementia. Vinpocetine, chemically known as ethyl apovincaminate, is a vinca alkaloid that exhibits cerebral blood-flow enhancing and neuroprotective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 38 publications
0
63
0
7
Order By: Relevance
“…Vinpocetine was originally discovered and marketed in 1978 under the trade name Cavinton, and it has been used widely in many countries for treatment of cerebrovascular disorder, such as stroke and cognitive impairment, because of its beneficial cerebrovascular effect and neuroprotective profile. To date, there have been no reports of significant side effects and toxicity related to vinpocetine treatment at therapeutic doses, and various clinical studies have demonstrated that vinpocetine is safe for long-term use (41). Thus, vinpocetine has long been considered an interesting compound that constantly attracts scientists and clinicians to investigate its novel therapeutic scheme in the fields of neuropsychiatry, ophthalmology, and otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…Vinpocetine was originally discovered and marketed in 1978 under the trade name Cavinton, and it has been used widely in many countries for treatment of cerebrovascular disorder, such as stroke and cognitive impairment, because of its beneficial cerebrovascular effect and neuroprotective profile. To date, there have been no reports of significant side effects and toxicity related to vinpocetine treatment at therapeutic doses, and various clinical studies have demonstrated that vinpocetine is safe for long-term use (41). Thus, vinpocetine has long been considered an interesting compound that constantly attracts scientists and clinicians to investigate its novel therapeutic scheme in the fields of neuropsychiatry, ophthalmology, and otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were given the respective drugs at a dose of 0.1 mL/10 g body weight (BW) by oral gavage once daily for 28 d. Doses of vinpocetine and treatment period were based on the clinical dosage in patients. 1,2) Behavioral Procedures According to the experiment protocol, learning and memory were assessed by three separate tests: "Open field, Y-maze, and fear conditioning tests." Training or testing was performed on 26th, 27th, and 28th d between 10.00 and 16.00 h in a light-and sound-controlled room (Table 1).…”
Section: Clinical Dose Conversionmentioning
confidence: 99%
“…Discovered in the late 1960 s, 1) it is currently popular in China and Hungary for treating cerebral ischemia. Its structure is shown in Fig.…”
mentioning
confidence: 99%
“…Âèíïîöåòèí óìåíüøàåò ñîïðîòèâëåíèå â ñîñóäàõ ãî-ëîâíîãî ìîçãà è óâåëè÷èâàåò êðîâîòîê â ïîñëåäíèõ, îñëàáëÿÿ ãèïî-ïåðôóçèþ. Ýòîò ýôôåêò òàêaeå âîâëå÷åí â îñóùåñòâëåíèå íåéðîïðîòåêòîðíîãî äåéñòâèÿ ïðåïà-ðàòà [56]. Âàaeíûì ýëåìåíòîì âëèÿíèÿ âèíïîöåòèòíà íà ñîñóäû ÿâëÿåòñÿ åãî ñïîñîáíîñòü ïîäàâëÿòü ïðîëè-ôåðàöèþ ÃÌÝ [50].…”
Section: ýêCïåpèìåíòàëüíàÿ è êëèíè÷åCêàÿ ôàPìàêîëîãèÿ 2015 òîì 78 ¹ 1unclassified